Variabilidade espacial e temporal de atributos químicos do solo em povoamento de eucalipto - Pereira, Daniel Pena (2014)
In recent years, increased adoption of precision forestry techniques in planted forests in Brazil were observed. The eucalyptus plantations occur preferentially in areas with low soil fertility and hence low productivity. Therefore, to achieve the maximum